Urinary neopterin concentration and toxicity of radiotherapy in patients with head and neck carcinoma during external beam radiation - Holečková, Petra; Krčmová, Lenka; Létal, Jiří; Svobodník, Adam; Kalábová, Hana; Kašparová, Markéta; Plíšek, Jiří; Pála, Miloslav; Vítek, Pavel; Solichová, Dagmar; Zezulová, Michaela; Študentová, Hana; et al. (Anticancer research, 2013)
AIM: Increased serum or urinary concentrations of neopterin are predictive of poor prognosis in patients with tumors across a spectrum of primary locations. Less information is available about the significance of changes of urinary neopterin concentrations during therapy. The aim of the present study was to examine the association between urinary neopterin and toxicity of radiotherapy. PATIENTS AND METHODS: We analyzed changes of urinary neopterin and toxicity of therapy in 12 patients with head and neck carcinoma during external-beam radiation. Urinary neopterin was determined daily by high-performance liquid chromatography. RESULTS: In addition to a trend for increased neopterin concentrations during radiation therapy, a significant association between changes of neopterin and toxicity and vice versa was observed with a rise of neopterin predicting a later manifestation of toxicity as well as manifestion of toxicity predicting a later rise of neopterin. CONCLUSION: Urinary neopterin is predictive of toxicity in patients with head and neck carcinoma. An association between toxicity and subsequent rise of urinary neopterin concentrations was also observed.
Keywords: senioři; Male; Female; Aged; neopterin; Middle Aged; Head and Neck Neoplasms; spinocelulární karcinom; Radiotherapy; Chromatography, High Pressure Liquid; mužské pohlaví; ženské pohlaví; Adult; Carcinoma, Squamous Cell; toxicity; Neopterin; vysokoúčinná kapalinová chromatografie; dospělí; radiotherapy; nádory hlavy a krku; lidé středního věku; lidé; radioterapie; Humans; Head and neck carcinoma